Türkiye’de Yapılmış Medya ve İletişim Çalışmaları Doktora Tezlerinde Teknoloji ve İnsan İlişkisi Üzerine Bir Değerlendirme - BABACAN, MEHMET EMİN (My University, 2022)
This study focuses on the establishment of relations between communication technologies and humans in doctoral dissertations conducted in the last fifty years, when media and communication studies have become prominent as an independent field in Turkey. In this sense, it seeks to reveal the way in which technology in general and the relations between communication technologies and humans in particular have been tackled in doctoral dissertations. The dissertations have been identified through a keyword search in the YÖK database including “communication technologies,” “new communication technologies,” and “media and communication”. This article provides a general evaluation of media and communication studies conducted in Turkey by focusing on the way in which twenty-two doctoral dissertations, completed in different universities and departments in different time intervals, have approached the relationship between communication technologies and humans on the basis of subject, purpose, scope and method. The data obtained through qualitative-quantitative content analysis method reveals that they have each handled the question in different ways. At the same time, this article has concluded that only a few studies have focused on the existential status of humans, while there has been more focus on change and impact in various areas of new communication technologies such as different concepts, institutions, sectors and processes.

Bu çalışma Türkiye’de medya ve iletişim çalışmalarının müstakil bir alan olarak daha belirgin hale geldiği son yarım yüzyılda yapılmış doktora tezlerinde iletişim teknolojileri ve insan ilişkisinin nasıl kurulduğuna odaklanmaktadır. Bu anlamda YÖK veri tabanında ‘iletişim teknolojileri, yeni iletişim teknolojileri, medya ve iletişim’ anahtar kelimeleri etrafında yapılan arama sonucunda ulaşılan tezlerde genelde teknoloji, özelde iletişim teknolojileri ve insan ilişkisinin ele alınma biçimi araştırılmaktadır. Makalede farklı tarih, üniversite ve ana bilim dallarında yürütülmüş yirmi iki doktora tezinin ‘konu, amaç, kapsam ve yöntem’ başlıkları etrafında iletişim teknolojileri ve insan ilişkisinin ele alınma biçimlerine odaklanılarak Türkiye’de yürütülen medya ve iletişim çalışmalarına ilişkin bir değerlendirme yapılmaktadır. Nicel-nitel içerik analizi tekniği ile elde edilen bulgular sonucunda tezlerin hemen hepsinde iletişim teknolojileri ve insan ilişkilerinin farklı biçimlerde ele alındığı anlaşılmaktadır. Bununla birlikte değerlendirilen tezlerde insanın varoluşsal konumunun az sayıda tezde tartışılmaya açıldığı, buna karşılık yeni iletişim teknolojilerine ilişkin daha çok farklı kavram, kurum, sektör, süreç gibi alanlarda değişim ve etki boyutlarının çalışıldığı sonucuna ulaşılmıştır.
An Evaluation on Relations Between Technology and Humans in Media and Communication Studies Dissertations in Turkey
Keywords: Medya ve İletişim; İletişim Çalışmaları; İletişim Teknolojileri; Teknoloji; İnsan; Media and Communication; Communication Studies; Communication Technologies; Technology; Human